2015
DOI: 10.1016/j.jelekin.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic assessment of muscle fatigue in massive rotator cuff tear

Abstract: Shoulder muscle fatigue has not been assessed in massive rotator cuff tear (MRCT). This study used EMG to measure fatigability of 13 shoulder muscles in 14 healthy controls and 11 patients with MRCT. A hand grip protocol was applied to minimise artifacts due to pain experience during measurement. The fatigue index (median frequency slope) was significantly non-zero (negative) for anterior, middle, and posterior parts of deltoid, supraspinatus and subscapularis muscles in the controls, and for anterior, middle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 67 publications
1
33
0
Order By: Relevance
“… Methods used: A/D = analog‐to‐digital conversion; Fmax = maximum force; MDF = median frequency. Mean differences: positive values indicate RCT group had greater values than the control or asymptomatic group. Cordasco et al [33]: Positive value means asymptomatic RC group had a greater %MVC compared with the symptomatic %MVC RCT group. Duc et al [25]: Positive value means control group had longer duration of EMG activity relative to movement time; negative value means RC group had longer duration. Hawkes et al [34]: Positive values means RC group had greater average EMG amplitude (normalised to means) compared with controls. Hawkes et al [26]: Positive value means that RC group had greater fatigue, shown as MDF slope (%/min), compared with controls. RCT = rotator cuff tear; MRI = magnetic resonance imaging; US = ultrasound; SSP = supraspinatus; ISP = infraspinatus; SUBS = subscapularis; UT = upper trapezius; LD = latissimus dorsi; PM = pectoralis major; SA = serratus anterior; AD = anterior deltoid; MD = middle deltoid; PD = posterior deltoid; MVIC = maximal voluntary isometric contraction; SD = standard deviation; MVC = maximum voluntary contraction; AR = activation ratio; TM = teres major; DE = deltoid; SIS = subacromial impingement syndrome; GHJ = gleno‐humeral joint; BB = biceps brachii; Br = brachioradialis; RMS = root mean square.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“… Methods used: A/D = analog‐to‐digital conversion; Fmax = maximum force; MDF = median frequency. Mean differences: positive values indicate RCT group had greater values than the control or asymptomatic group. Cordasco et al [33]: Positive value means asymptomatic RC group had a greater %MVC compared with the symptomatic %MVC RCT group. Duc et al [25]: Positive value means control group had longer duration of EMG activity relative to movement time; negative value means RC group had longer duration. Hawkes et al [34]: Positive values means RC group had greater average EMG amplitude (normalised to means) compared with controls. Hawkes et al [26]: Positive value means that RC group had greater fatigue, shown as MDF slope (%/min), compared with controls. RCT = rotator cuff tear; MRI = magnetic resonance imaging; US = ultrasound; SSP = supraspinatus; ISP = infraspinatus; SUBS = subscapularis; UT = upper trapezius; LD = latissimus dorsi; PM = pectoralis major; SA = serratus anterior; AD = anterior deltoid; MD = middle deltoid; PD = posterior deltoid; MVIC = maximal voluntary isometric contraction; SD = standard deviation; MVC = maximum voluntary contraction; AR = activation ratio; TM = teres major; DE = deltoid; SIS = subacromial impingement syndrome; GHJ = gleno‐humeral joint; BB = biceps brachii; Br = brachioradialis; RMS = root mean square.…”
Section: Resultsmentioning
confidence: 98%
“…Hawkes et al [26]: Positive value means that RC group had greater fatigue, shown as MDF slope (%/min), compared with controls.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The deltoid, biceps and triceps muscles played important roles in stabilizing the shoulder joint during static arm exertions. (Hawkes et al, 2015;Itoi et al, 1993).…”
Section: Muscle Selectionmentioning
confidence: 99%